Immuno and Cytochemical Localization of Trypanosoma cruzi Nitric Oxide Synthase - Goldstein Raij, Jorge (2000)
The localization and subcellular disstribution of Trypasoma cruzi  nitric oxide synthase was investigated in epimastigote cells by immunocytochemistry at electron and light microscope level, using a polyclonal antibody to neuronal nitric oxide synthase, and also, at light microscope level, by NADPH-daiphorase histochemical reaction. The immunoreactivity was ultrastructutrallu localized  by EM in the inner surface of cell membranes and in free cytosolic clusters in the body, flagellum and apical extreme. Light microscopy showed that immunoprecipitates, specific for Trypanosoma cruzi nitric oxide synthase, co-localized with the formazan precipitates generated by the diaphorase reaction in the same areas identified by electron microscopy. These results, taken together with previous finfing from our laboratory could help to explain the involvement of the nitric oxide transduction pathway in T. cruzi epimastigote motility.